Does the PillCam SB3 capsule endoscopy system improve image reading efficiency irrespective of experience? A pilot study - Omori, Teppei; Hara, Toshifumi; Sakasai, Sachiyo; Kambayashi, Harutaka; Murasugi, Shun; Ito, Ayumi; Nakamura, Shinichi; Tokushige, Katsutoshi (Endoscopy International Open, 2018)
Background and study aims The aim of this study was tp compare the diagnostic efficiency of the PillCam SB3 capsule endoscopy (CE) system with the older system, PillCam SB2, taking into consideration the experience of the image reader. Patients and methods Small intestinal CE was conducted on 64 patients around May 2014 when the SB3 was introduced in our hospital. Data obtained from 20 patients (SB2: 10 and SB3: 10) based on transit time were assessed by junior (experience: 20 images), intermediate (> 50), and expert readers (> 600). Results Reading time with the CE down to the end of the small intestine was shorter in the SB3 group for each reader (SB2 vs. SB3: junior, 40.2 ± 10.1 vs. 23.7 ± 6.7 [P = 0.0009]; intermediate, 21.4 ± 4.9 vs. 10.3 ± 2.9 [P = 0.0003]; expert, 23.2 ± 5.6 vs. 11.1 ± 2.9 min [P = 0.0002]). Interpretation agreement rates between the findings by junior and intermediate readers and those by the expert reader were 84.6 % and 92.3 %, respectively. For the junior reader, rates of agreement using the SB2 and SB3 systems with those by the expert reader were 85.7 % and 83.3 %, respectively; no significant difference was noted between the two systems. Similarly, for the intermediate reader, the respective agreement rates using the SB2 and SB3 systems were 85.7 % and 100 %, respectively. Conclusions The PillCam SB3 reduces the time burden on readers irrespective of their experience.